Remarks on biology, vocalisations and systematics of Urocynchramus pylzowi Przewalski (Aves, Passeriformes) - Gebauer, Axel; Kaiser, Martin; Wassmann, Christine (Zootaxa, 2006)
Several field studies in the Qinghai Nanshan area (Qinghai Province, China) have added new findings to the scant knowledge about Przewalski´s Rosefinch Urocynchramus pylzowi Przewalski, 1876. The hitherto completely unknown vocalisations are described and used to clarify systematic relationships. Although one could argue for a relationship to Uragus sibiricus (Pallas), based on nearly identical auditory impression and sonagram structures of their songs, detailed measurements show significant differences in time and frequency parameters. Moreover a mtDNA analysis shows no close phylogenetic relationship to either of three major emberizid clades. These results support the hypothesis that Urocynchramus belongs in its own family, the Urocynchramidae.